2016
DOI: 10.12816/0023354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warm Saline on Bleeding during Sinus and Septum Surgery

Abstract: Objective: To assess the effect of warm saline on bleeding and surgical field visibility during endoscopic sinus surgery and septorhinoplasty. Methods: The study included 100 patients, of both males and females, aged 28-58 years, classed I and II by the American Society of Anesthesiologists (ASA), and assigned for elective functional endoscopic sinus surgery and septorhinoplasty under general endotracheal induced hypotensive anesthesia, at King Hussein Hospital, King Hussein Medical City (KHMC), Amman, Jordan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(57 citation statements)
references
References 8 publications
0
57
0
Order By: Relevance
“…The Boezaart score is a scale assigning a numerical value from 0 to 5, used to measure the degree of endoscopic impairment of intraoperative bleeding that occurs. 5 A similar study by Gan et al showed that the use of warm saline irrigation at 49°C was correlated with a reduced blood loss. Bleeding rate was 1.7 milliliters per minute whereas the use of saline at 18°C correlated with blood loss of 2.3 milliliters per minute.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The Boezaart score is a scale assigning a numerical value from 0 to 5, used to measure the degree of endoscopic impairment of intraoperative bleeding that occurs. 5 A similar study by Gan et al showed that the use of warm saline irrigation at 49°C was correlated with a reduced blood loss. Bleeding rate was 1.7 milliliters per minute whereas the use of saline at 18°C correlated with blood loss of 2.3 milliliters per minute.…”
Section: Discussionmentioning
confidence: 82%
“…Warm saline irrigation with a temperature of up to 50 o C can reduce of sinonasal mucosal blood from small vessels. 5 This method was first introduced by obstetricians to control postpartum hemorrhage more than 100 years ago. In the field of rhinology this method was used by Guice and Fayette in 1878 to treat epistaxis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Hot saline irrigation has previously been used as treatment in epistaxis, 8 postadenoidectomy haemorrhage, 9 post-partum haemorrhage 10 and more recently the technique has been utilised in FESS. [11][12][13] The haemostatic mechanism of hot saline irrigation is still poorly understood. However, Stangerup and Thomsen found that rabbit nasal mucosa exposed to water at a temperature of 50°C led to mucosal oedema and dilatation of capillary vessels without any detrimental toxic effects or necrosis.…”
Section: Introductionmentioning
confidence: 99%